Exploring ischemic stroke based on the ferroptosis perspective: ECH1 may serve as a new biomarker and therapeutic target - Qu, Rendong; Zhang, Yiyan; Zhang, Haojia; Li, Ke; Zhang, Boning; Tong, Hongxuan; Lu, Tao (Frontiers in Neuroscience, 2025)
BackgroundIschemic stroke (IS), the leading stroke subtype (∼87%), arises from vascular occlusions, triggering brain necrosis through ischemia-reperfusion injury. Ferroptosis, an iron-driven cell death via Fe2+-mediated lipid peroxidation, is implicated in IS pathology. This study demonstrates that enoyl-coA hydrolase 1 (ECH1) may serve as a peripheral biomarker and therapeutic target for IS based on ferroptosis signaling.MethodsWe integrated transcriptome data from the GEO database with preprocessing and normalization. Hub genes were screened using differential expression analysis and machine learning algorithms. Subsequently, genes were further filtered by mendelian randomization and also validated using transient middle cerebral artery occlusion (tMCAO) model.ResultsFerroptosis-related genes in the IS group showed higher expression compared with the healthy control group. Using differential expression analysis and machine learning algorithms, 12 potential hub genes were successfully screened. Mendelian randomization analysis further confirmed the causal association between ECH1 and stroke. In the tMCAO mouse model, ECH1 mRNA levels were down-regulated, consistent with the results of the clinical samples.ConclusionIn this study, taking ferroptosis as an entry point, ECH1 may serve as a potential peripheral blood biomarker and therapeutic target for IS through multidimensional validation, providing a basis for the development of relevant precision diagnostic strategies.